Pathfinder - Card, Orson Scott (New York : Simon Pulse, 2010)
Thirteen-year-old Rigg has a secret ability to see the paths of others' pasts, but revelations after his father's death set him on a dangerous quest that brings new threats from those who would either control his destiny or kill him.
Booklist starred
Bulletin of the Center for Children's Books starre
School Library Journal
Booklist starred, November 2010
Bulletin of the Center for Children's Books starre, December 2010
Horn Book, May 2011
Keywords: Identity (Psychology) -- Juvenile fiction; Interplanetary voyages -- Juvenile fiction; Psychic ability -- Juvenile fiction; Space colonies -- Juvenile fiction; Time travel -- Juvenile fiction; Identity -- Fiction; Interplanetary voyages -- Fiction; Psychic ability -- Fiction; Science fiction; Space colonies -- Fiction; Time travel -- Fiction; Identity (Psychology) -- Fiction; Interplanetary voyages -- Fiction; Parapsychology -- Fiction; Science fiction; Space colonies -- Fiction; Time travel -- Fiction; Science fiction